Use of a novel coinfection system reveals a role for Rac1, H-Ras, and CrkII phosphorylation in Helicobacter pylori-induced host cell actin cytoskeletal rearrangements - Brandt, Sabine; Shafikhani, Sasha; Balachandran, Priya; Jin, Shouguang; Hartig, Roland; König, Wolfgang; Engel, Joanne; Backert, Steffen (FEMS Immunology and Medical Microbiology, 2007)
The Helicobacter pylori CagA protein induces profound morphological changes in the host cytoskeleton and cell scattering, but the signalling involved is poorly understood. Pseudomonas aeruginosa also affects host actin cytoskeleton in a variety of ways by injecting the ExoS and ExoT toxins which encode N-terminal GTPase activating protein and C-terminal ADP-ribosyltransferase (ADPRT) activities. In this study we developed a novel coinfection assay to gain new insights into CagA effector protein functions. We found that P. aeruginosa injecting either ExoT or ExoS efficiently prevented the H. pylori-induced scattering phenotype. Both the Rho-GAP and the ADPRT domains of ExoS were needed to block the H. pylori-induced actin cytoskeletal rearrangements, whereas either domain of ExoT was sufficient for this activity. This strategy revealed common pathways subverted by different pathogens, and aided in the definition of signalling cascades that control the CagA-mediated cell scattering and elongation. We identified Crk adapter proteins, Rac1 and H-Ras, but not RhoA or Cdc42, which are the ExoS and/or ExoT targets, as crucial components of the CagA-induced phenotype. In addition, we show that ADP-ribosylation of CrkII by ExoT blocks phosphorylation of CrkII at Y-221, which is also important for the CagA-induced signalling. © 2007 Federation of European Microbiological Societies.
Created from Fastlane, Scopus look-up
Keywords: Helicobacter pylori; Molecular pathogenesis; Pathogenicity island; Pseudomonas aeruginosa; Toxin; Type III and type IV secretion